Microwave Magnetoelectric Devices - A. S. Tatarenko; M. I. Bichurin (Advances in Condensed Matter Physics)
Tunable microwave magnetoelectric devices based on layered ferrite-ferroelectric structures are described. The theory and experiment for attenuator, band-pass filter and phase shifter are presented. Tunability of the ME devices characteristics can be executed by application of an electric field. This electric tuning is relatively fast and is not power-consuming. The attenuator insertion losses vary from 26 dB to 2 dB at frequency 7251 MHz. The tuning range of 25 MHz of band-pass filter at frequency 7360 MHz was obtained. A maximum phase shift of 30–40 degree at the frequency region 6–9 GHz was obtained.